Role of the 26S Proteasome and Posttranslational Modifications in Regulating the Expression of Retinoic Acid-Responsive Genes - Higazi, Aliaa M. (Université d'Ottawa / University of Ottawa, 2011)
Retinoic acid (RA) has been recognized as a chemotherapeutic agent for various malignances such as lung, skin as well as cervical cancers. It binds to retinoid receptors heterodimers and consequently activates several RA-responsive genes which are involved in many biological processes including vertebrate development, bone growth, vision, haematopoiesis, cell growth, differentiation and apoptosis. These genes are under the control of numerous regulators to ensure their timely ordered activities. Among these regulators, we focused here on the 26S proteasome and ubiquitination. It has been reported that the activity of the ubiquitin/proteasome system (UPS) plays a fundamental role in retinoic acid receptor (RAR)-regulated transactivation. The mechanisms underlying this role, however, remain to be established. Chromatin immunoprecipitation (ChIP) assays in our study demonstrated that the 26S proteasome activity is important for preserving the occupancy of a TATA box-containing RA-responsive promoters by liganded retinoid receptors and thus by their coactivators. Additionally, by using coimmunoprecipitation assays and by measuring the half-life of retinoid receptors, we found that the non-proteolytic function of the proteasome is required for ligand-dependent association between DNA-free RAR-α and both DNA-free RXR-α and coactivators. Moreover, using immunofluorescent staining and in vivo ubiquitination assays, a proteasome inhibition-dependent cytoplasmic localization of RAR-α as well as ligand-enhanced ubiquitination and stabilization of RAR-α were shown. Our findings therefore, define novel mechanisms by which the UPS controls RAR-regulated genes. Furthermore, we shed new light on the regulators of retinoid receptors ubiquitination and subcellular localization.
Keywords: RAR; RARE; proteasome; ubiquitination; P19 cells; gene transcription